Diagnosis Between Chaos and Control: Affect and Hospital Clinicians' and Older Adult Patients' Narratives of Urinary Tract Infections - Saukko, Paula M.; Rousham, Emily Kate (Frontiers in Sociology, 2020)
Research has observed that older adults are frequently overdiagnosed with urinary tract infection (UTI) and unnecessarily prescribed antibiotics in hospitals. In this article we explore the overlooked affective dimension of experiences of diagnosis and prescribing. Drawing on interviews with doctors, nurses and older adult patients (n=41) on UTI diagnosis in two UK hospitals and Arthur Frank’s work on illness narratives we identified two affective ways of experiencing diagnosis. Some clinicians and older adult patients articulated chaos narratives about being overwhelmed by contradictory evidence and events, doubting the repeated UTI diagnoses and courses of antibiotics but being unable to do anything about their concerns. Other clinicians and patients articulated control narratives about UTIs being frequently diagnosed and antibiotics prescribed to restore patients’ health, echoing certainty and security, even if the processes described typically did not follow current guidance. We contend that analysing the affective dimension offers conceptual insights that push forward sociological discussions on diagnosis as reflective or dogmatic in the context of the contradiction between acute care and chronic illnesses of old age. Our findings contribute practical ideas of why overdiagnosis and overprescribing happen in hospitals and complicate notions of patients pressuring for antibiotics. We also present methodological suggestions for analysing how participants tell about their experiences in order to explore the typically not directly spoken affective dimension that influences thoughts and actions about diagnosis.